Application of RAPD-PCR technology in determining the genetic variation of local cows in Babylon Governorate (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
The present study to find out the genetic distance between two breeds from Babylon cattle (Holstein crossbred with local breed and Restaky local breed). Polymer chain reaction DNA were used after DNA extraction from the blood of cattle, six primers were used in this study. The results of PCR were checked by used gel agaros, where taking the results of PCR and lowed on 0.8% from gel agaros to find out the quality and concentration of DNA. All the primers that used in RAPD-PCR technique for DNA extraction to two breeds were succeeded, (1.25±0.8). The overall average genetic distance was 1.25±0.8 between these two breeds, while the average percentage differences were estimated for all primers to these two breeds (63.3±1.33).